Sea urchin prosome: characterization and changes during development. - Akhayat, O (1987)
A cytoplasmic particle displaying properties in common with a structure present in duck erythroblasts, termed the prosome, has been isolated from eggs and embryos of two species of sea urchin. This particle was partially purified by sedimentation in sucrose gradients containing 0.5 M KCl, and some of its physical properties and its behavior during early development were determined. The prosome sediments between 16 and 19 S and has a buoyant density of 1.30 g/cm3 in Cs2SO4 gradients. Biochemically, the particle is characterized as 20-25 polypeptides of molecular size 24-35 kDa with about 10 small RNAs. A monoclonal antibody directed against the 27-kDa protein of duck erythroblast prosome recognizes a 27-kDa protein of the sea urchin prosome. We have used this protein, as representative of the prosome, to immunologically determine the level and the subcellular localization of the particle during development. Immunoblotting and cellular fractionation studies show that the 27-kDa prosome polypeptide is present almost entirely in the postribosomal supernatant of unfertilized egg lysates. After fertilization and during early development, the total amount of 27-kDa protein per embryo remains constant, but the amount in the postribosomal supernatant decreases; there is a concomitant increase in the level of the 27-kDa protein in a rapidly sedimenting, particulate fraction containing nuclei. Immunofluorescence studies further show that the 27-kDa protein is located mainly in the cytoplasm of eggs and two-cell embryos. The subcellular location of the prosome, therefore, appears to change during development. In vivo labeling experiments have failed to detect the synthesis of either the prosome proteins or RNAs in eggs and embryos up to 48 hr of development, suggesting that this cytoplasmic particle is not synthesized de novo in early embryogenesis and thus is metabolically stable. The prosome is thus a normal cellular constituent of the sea urchin and is most likely synthesized during oogenesis and stored in the unfertilized egg.